PENGARUH GAYA KEPEMIMPINAN LURAH TERHADAP KEPUASAN KERJA APARAT KELURAHAN BAHU KECAMATAN MALALAYANG KOTA MANADO - ., YULIYANTI; RORONG, ARIE JUNUS; TAMPI, GUSTAAF BUDI (JURNAL ADMINISTRASI PUBLIK, 2018)
Leadership style of boss can influence the success of employees in achievement. In other words,leadership style of boss can influence on job satisfaction of employees in an organization. Be purpose ofresearcher who want to achieve in this research is to know how big influence of leadership style of lurah tojob satisfaction of kelurahan Bahu Kecamatan Malalayang Kota Manado. The method used in this researchis quantitative method, with correlation and regression approach. In this research, the variables used arethe leadership style of lurah as independent / independent variable while the job satisfaction of the apparatusas dependent variable. So the sample in this research is all apparatus of Sub-District of Bahu KecamatanMalalayang Manado City amounting to 15 people. The result of this research is Head of Lurah Leadershipstyle have negative effect to the Satisfaction of Sub-District Officer of Sub-District of Malalayang City ofManado which is shown by regression equation Å¶ = 27.513 - 0.058X + e and hypothesis test with t-test thatimplies that value (-0.211) less than ttab value (1.771) at error level of 5% and dk = 13 for acceptance of theHo and the rejection of HA. Besar influence is shown by the coefficient of determination of 0.003 whichcontains the meaning of 0.03%Keywords: Lurah Leadership Style, Job Satisfaction Apparatus